(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
Narrative text is a text that is designed to entertain the readers. In the Indonesian educational context, the students lack general exposure to how to make an effective narrative text. This study is aimed at analyzing a student’s narrative text. The study participant was a second-grade private Islamic High School student in Semarang Regency. She was selected as the participant since her writing showed her as a low achiever, which may portray the whole class’s ability. Document analysis was employed to obtain adequate information on the student’s narrative writing viewed from the SFL. The findings indicate that the student lacks grammar, ellipses in finite nominal sentences, L1 interference with word order, and vocabulary mastery. Therefore, to minimize the recurring problems, problem-based learning is one of the best approaches to teaching narrative writing. It is used since it conveys various activities in which the students are motivated to write and share their knowledge with others in collaborative learning. Thus, to implement problem? based learning into the teaching and learning process, the steps in teaching problem-based learning should be blended into the genre-based approach.